(untitled) (Jurnal Geomine, 2015)
Modeling of the stone recivitate is a way to find out the conditionof precipitate and the speread pattern of the coal seam. The aim of this research is to find out the thickening directions and the spread pattern of the coal seam in area pit 1 block 13 of Rimau Energy Mining Corporatio. The research method that used to made the model of the coal precipitate is by processing the drilling log data that consist the name of each drilling point, the coordinat of each drilling point, the thickness of the coal seam, and the lithology using Mincom Minescape 411.8 software to find out the model of the coal precepitate and using Surfer 10 software to find out the Isopach maps. The model of coal seam’s precipitate produce 6 coal seam’s which are seam 1, seam 2, seam 3, seam 4, seam 5, and seam 6 with the general direction of the coal spread is northwest-south-southwest and the declitivityto the east is about 14-16 degree with the range of the thickness of each seam’s are seam 1: 0.43 meter, seam 2: 0.36 meter, seam 3: 1.88 meter, seam 4: 1.26 meter, seam 5: 1.36 meter, and seam 6: 2.14 meter.